Optimal control of batch reactors using generic model control (GMC) and neural network - Aziz, N.; Hussain, Mohd Azlan; Mujtaba, I.M. (Elsevier, 2000)
On-line implementation of the optimal reactor temperature profiles in batch reactors is considered here. The optimal reactor temperature profiles are obtained by solving dynamic optimisation problems off-line to achieve maximum conversion to the desired product. Generic Model Control (GMC) algorithm is used to design the controller to track the optimal temperature profiles (dynamic set points). Neural Network technique is used as the on-line estimator to estimate the amount of heat released by the chemical reaction. A complex reaction scheme is considered in this work to illustrate the ideas. The results clearly show that the GMC controller coupled with a Neural Network based estimator tracks the optimal temperature profiles very well to obtain the desired products on target.